Pharmacokinetics and pharmacodynamics of ciprofol after continuous infusion in elderly patients - Xiaowen Guo; Yang Qiao; Sijie Yin; Fengqin Luo; Lingmei Yi; Jiajia Chen; Man Lu (BMC Anesthesiology)
Abstract Background Ciprofol, a novel intravenous anesthetic, which has primarily been used for the induction and maintenance of general anesthesia in adults, is characterized by rapid onset, short duration of action, and quick and smooth recovery. However, the pharmacokinetic characteristics of continuous infusions and the correlation between the plasma concentration and the bispectral index (BIS) in elderly patients are still unknown. Method In this randomized, controlled study, thirty elderly patients (62–78 years old) undergoing elective gastrointestinal tumor resection were treated with propofol (N = 15) or ciprofol (N = 15) as sedatives during anesthesia. After induction, ciprofol/propofol was continuously infused intravenously until the end of the operation. Perioperative vital signs, injection pain, adverse events (AEs), BIS values, eyelid reflex disappearance times, and recovery times were recorded. The plasma concentrations of ciprofol and propofol were measured by liquid chromatography tandem mass spectrometry (LC‒MS/MS) and the pharmacokinetics were determined by noncompartmental analysis. Results Both drugs caused a decrease in blood pressure and heart rate after induction. Eight cases (53. 3%) of hypotension and 3 cases (20%) of bradycardia occurred in the propofol group, while 8 cases (53. 3%) of hypotension and 5 cases (33. 3%) of bradycardia occurred in the ciprofol group. At intubation, the ciprofol group experienced fewer fluctuations in blood pressure than the propofol group. Ciprofol resulted in only one case (6.7%) of mild injection pain, less than that produced by propofol (10/15, 66.7%) (P < 0.05). Anesthesia induction was successfully completed with both drugs, and there were no significant differences in eyelash reflex disappearance or recovery time between the two groups. The plasma concentrations during maintenance were relatively stable in both groups (propofol 1.78 ± 0.67 μg/mL, ciprofol 0.71 ± 0.23 μg/mL), and a suitable depth of sedation was achieved with a BIS of 40–60. The pharmacokinetic (PK) parameters for ciprofol are listed as follows: Maximum Plasma Concentration (Cmax) 6.02 ± 2.13 μg/ml; Time to Maximum Concentration (Tmax) 0.18 ± 0.62 min; Apparent Volume of Distribution (Vz) 3.96 ± 0.84 L/kg; Total Clearance (CL) 0.83 ± 0.14 L/h/kg; Half-life (t½) 3.47 ± 1.85 h; Area Under the Curve (AUC) 5000 ± 900 L/h/kg; Terminal Elimination Rate Constant (λz) 0.23 ± 0.07 1/h. Similar to propofol, the plasma concentration of ciprofol was linearly correlated with the BIS. Conclusion Ciprofol, a novel intravenous anesthetic, can be safely and effectively used in elderly patient continuous infusion with minimal injection pain. Plasma concentrations of ciprofol correlate well with BIS values, helping control sedation depth. For elderly patients undergoing gastrointestinal tumor surgery, an optimal maintenance dose of 0.8 mg/kg/h is recommended. Trial registration This clinical trial (registration No: ChiCTR2100047580, https://www.chictr.org.cn . The pre-registration date was June 20, 2021, and the review approval and official case solicitation began in December 2021; Retrospectively registered) was conducted in accordance with the World Medical Congress Declaration of Helsinki and Good Clinical Practice guidelines. All study subjects provided written informed consent.